Acid‐Hydrolyzed Gliadins Worsen Food Allergies through Early Sensitization. Issue 17 (30th July 2018) - Castan, Laure; Villemin, Clélia; Claude, Mathilde; Aubert, Philippe; Durand, Tony; Neunlist, Michel; Brossard, Chantal; Magnan, Antoine; Bodinier, Marie; Bouchaud, Grégory
Abstract : Scope: Food allergies result from a complex immune response involving both innate and adaptive immune cells. Major proteins of wheat flour, gliadins, appear to be important allergens, and their characteristics can influence the allergic response. This study investigates the immune reaction when developing a food allergy to gliadins in native, deamidated, or hydrolyzed forms. Methods: The immune response after one or two intraperitoneal sensitizations and after oral challenge with each gliadin form is analyzed. Results: Results demonstrate that deamidated gliadins induce a stronger allergic reaction compared to native gliadins. Moreover, deamidation induces an earlier increase in intestinal permeability associated with more pronounced Th2 and Th17 polarizations together with an influx of antigen‐presenting cells, especially cDC2. Conclusion: Altogether, Results indicate that industrial processes such as deamidation or hydrolysis influences food allergenicity through immune modulation and helps us to develop tools to determine how these processes can influence this reaction and encourage or decrease allergic reactions. Abstract : Major proteins of wheat flour, gliadins, are important allergens and their characteristics can influence the allergic response. The immune reaction when developing a food allergy to gliadins under different form is investigated. Results demonstrate that deamidation worsens the allergic reaction, whereas hydrolyzation displays a minor effect.